APPLYING CANVAS TO ASSESS MOVABLE THERAPY SPA BUSINESS MODEL – CASE RESEARCH IN DANANG - Trinh, Le Tan; Nguyen, Duc Tri; Dao, Thi Dai Trang; Thai, Nu Ha Uyen (INTI International University, 2022)
The movable therapy spa business is a business model that is portable and caters to busy customers who cannot go to spas to enjoy themselves. This model will help you relax and dispel fatigue. In addition, we use vehicles to move to the spa, which is very attractive to customers because this is a new business form. The author used canvas to solve problems because it has a lot of advantages. Method: Qualitative research (depth interview) to get information related to the components in the Canvas model. We have studied the documents related to the spa's services and information. Besides, we also research and learn from managers or supervisors in spa therapy and researchers or entrepreneurs in the Movable Business Spa to give customers the best feelings when experiencing our spa. Next, it filled the interior of the car with spa tools that are contemporary, high-quality equipment because of the ambition to earn the clients' loyalty, even the most fastidious people. And above all, the authors have a professional team for consulting customers with the most enthusiasm. The study will help business construct new spa model effectively.